Kinerja Pelaksanaan Ronde Keperawatan Metode 8p Terhadap Kualitas Pelayanan Keperawatan di Rumah Sakit Premier Jatinegara Jakarta - Khusaeni, Agus; Hadi, Muhammad; Naryati, Naryati; Suminarti, Tini (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Nursing is a profession with a professional function to help identify and address the immediate needs of patients and provide assistance to meet those needs. Hourly Rounds are performed using the “8P” method, which includes: Pain, Potty (bathroom needs), Position (patient position), Pump (infusion pump), Periphery (environment), Plan (action plan), Possessions (patient belongings security), and Parting (rechecking patient needs before leaving the room). This method is expected to identify patient needs. This study aims to identify the direct and indirect relationships between the performance of nursing rounds using the 8P method and the quality of nursing services at Premier Jatinegara Hospital.The method used in this study is descriptive analytic to analyze the direct and indirect relationships between the performance of nursing rounds using the 8P method and the quality of nursing services. The path analysis results found that out of five independent variables, four variables had significant relationships with the implementation of the 8P round: workload (p-value = 0.033), supervision (p-value = 0.008), leadership style (p-value = 0.013), and teamwork (p-value = 0.038). However, reward and punishment had no significant relationship with the implementation of the 8P round (p-value = 0.612). Based on the path analysis, it was found that workload and leadership style had both direct and indirect relationships with the quality of nursing services through the implementation of the 8P nursing round (p-value < 0.05).The conclusion of this study is that there is a direct and indirect relationship between the nurse's workload and the leadership style used toward the quality of nursing services through the implementation of the 8P nursing round. Keywords: Nursing Service Quality, Nursing Rounds, Performed, 8P Method.  ABSTRAK Keperawatan adalah suatu profesi yang mempunyai fungsi  profesional yaitu membantu mengenali dan menemukan kebutuhan pasien yang bersifat segera dan memberikan bantuan untuk pemenuhannya. Hourly Round yaitu ronde yang dilakukan dengan menggunakan “8 P” yaitu Pain (nyeri), Potty (kebutuhan ke kamar mandi), Position (posisi pasien), Pump ( alat infus yang terpasang), Periphery (lingkungan), Plan (rencana tindakan), Possesions (keamanan barang milik pasien) dan Parting (tanyakan kembali kebutuhan pasien sebelum meninggalkan ruangan) diharapkan dapat menemukan kebutuhan pasien. Penelitian ini dilakukan untuk mengidentifikasi hubungan langsung dan tidak langsung kinerja pelaksanaan ronde keperawatan metode 8p terhadap kualitas pelayanan keperawatan di Rumah Sakit Premier Jatinegara. Desain penelitian ini menggunakan deskriptif analitik untuk menganalisia hubungan langsung dan tidak langsung kinerja pelaksanaan ronde keperawatan metode 8p terhadap kualitas pelayanan keperawatan. Dari hasil path analysis jumlah sample 110 perawat ditemukan  lima variabel independent, empat variabel diantaranya memiliki hubunganyang signifan terhadap pelaksanaan ronde 8P yaitu bebn kerja (p-value = 0,033), Supervisi (p-value = 0,008), gaya kepemimpinan (p-value = 0,013), dan teamwork (p-value = 0,038). Sedangkan reward dan punishment tidak memiliki hubungan yang bermakna terhadap pelaksanaan ronde 8P(p-value = 0,612). Berdasarkan hasil Analisa Jalur didapatkan beban kerja dan gaya kepemimpinan memiliki hubungan langsung dan tidak langsung dengan kualitas pelayanan keperawatan melalui pelaksanaan ronde keperawatan 8P (p-value < 0,05). Terdapat hubungan langsung dan tidak langsung beban kerja perawat dan gaya kepemimpinan yang digunakan terhadap kualitas pelayanan keperawatan melalui pelaksanaan ronde keperawatan dengan metode 8P. Kata Kunci: Kinerja, Kualitas Pelayanan Keperawatan, Metode 8P, Ronde Keperawatan.